Antimicrobial activity of exocellular metabolites of Acinetobacter Calcoaceticus IMB B-7241, Rhodococcus Erythropolis IMB Ac-5017, Nocardia - Konon, Anastasia; Sofіlkanich (Morozova), Anna; Pirog, Tatiana (My University, 2012)
It was showed that exocellular metabolites of strains IMV B-7241, IMV Ac-5017 and K-8 inherent antimicrobial properties against some phytopathogenic microorganisms. Therefore, these preparations can be used as environmentally safe antimicrobial products, which exhibit high efficiency against a number of pathogenic bacteria resistant to existing traditional preparations.
Keywords: antimicrobial activity; антимікробна активність; exocellular metabolites; позаклітинні метаболіти; phytopathogenic microorganisms; фітопатогенні бактерії; кафедра біотехнології і мікробіології